THE ROLE OF TURKISH SCIENTIFIC AND ANALYTICAL CENTERS IN STUDYING THE HISTORY OF UZBEKISTAN (THE EXAMPLES OF TIKA AND TURKSOY) - S. Toshev (Western European Studies, 2024)
After the independence of the Central Asian republics, the interest in the history and culture of the peoples of the region increased. In the West, in Germany, France, England, the Russian Federation, the United States of America, and in Eastern countries such as India, Iran, China, Turkey, scientific centers dealing with the latest history of Uzbekistan have been established. In these centers, issues of the recent history of Uzbekistan that have not been studied or little studied in our national historiography are being researched, this period is being approached with a new perspective and interpretation. In particular, in Turkey, we can see great scientific interest in the history of Uzbekistan, especially the political, social, economic and cultural changes in the years of independence
Keywords: Central Asian Republics; Uzbekistan; Turkiye